PEMOLISIAN TERHADAP MARGINALISASI DAN EKSKLUSI SOSIAL DALAM PEMBANGUNAN PROYEK STRATEGIS NASIONAL DI PULAU REMPANG - Setiawan, Dony (Jurnal Ilmu Kepolisian, 2023)
Supporting and safeguarding government policies is one of the state ethics that must be implemented by Polri, which if not implemented is a violation of the Polri professional code of ethics. In securing government policies, Polri is often faced with the dilemma of serving the interests of the government or the public interest. For example, in securing the development of the National Strategic Project (PSN) on Rempang Island, the police were faced with a series of rejections and resistance from residents who felt marginalized, resulting in riots, damage to facilities, injuries, and allegations of human rights violations. To overcome this, it is necessary to identify the dimensions of marginalization and social exclusion that occur, the factors that cause them and the policing strategies needed to overcome them. Using a library research approach with a case study pragmatic paradigm and a literature search method, this research found that the marginalization and social exclusion that occurred were structural, multidimensional and relational, including political, legal and human rights, economic, social and cultural dimensions. The marginalization is caused by the development paradigm, the lack of recognition of the existence and rights of indigenous peoples and the police paradigm. To overcome this, it is necessary to apply problem-oriented policing so that marginalization and social exclusion do not develop to endanger the safety and security of citizens by working with stakeholders to overcome marginalization, social exclusion, discrimination and inequality that occur, overcoming the factors that cause and impact, building relationships and trusting communication, disseminating information needed by citizens, facilitating aspirations and encouraging citizen participation, recognition, respect and protection of the existence, identity and human rights and rights of indigenous peoples, seeking citizen approval or agreement on solutions that have been formulated together before starting the development stage.